Analisis dan Pemodelan Pencemaran Timbulan Sampah Menggunakan Aplikasi Integrated Waste Management 2 (IWM2) di Kawasan Pesisir Waha Raya, Kabupaten Wakatobi - Muhammad Irpan Sejati Tassakka; Alfi Kusuma Admaja; Indah Alsita; Kezia Gloria Apriliana Runtu; Martina Rahmadani (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
Waha Raya Coastal Area consists of 3 from 90 coastal villages in Wakatobi and included in tourism utilization zone. Currently, the waste management from community activities in there has not yet been optimal. This can affect the quality of coastal ecosystem and the economic value of tourism later. The aims of this paper are to estimate the total of waste generation, modeling the impact of pollution on water and air due to waste generation, and recommend the alternative sustainable waste management system in Waha Raya Coastal Area. The method of taking and measuring the sample of waste generation based on SNI 19-3964-1994, while method of analyzing waste management systems use the application of Integrated Wasted Management 2 (IWM2). After modeling the effects of pollution on water and air in 4 scenarios, it was found that the 4th scenario was able to reduce airborne particulate pollutants ammount 104.8 kg/year; CO2 of 102.6 kg year; CH4 36.0 kg/year; and 861.3 kg/year GWP. The 4th scenario is also able to reduce the level of water pollution those are BOD amount 146kg/year, COD amount 436 kg/year, SS 34 kg/year and Fe2+ 42 kg/year. The results indicate that the application of 4th scenario is able to be the alternative sustainable of waste management.